INTERNET FINANCIAL REPORTING: ANALYSIS OF LITERATURE ON EVOLUTION REPORTING CORPORATIONS IN THE INDUSTRY 4.0 ERA - Fityan Izza Noor Abidin; Endra Wahyu Ningdiyah; Wiwit Hariyanto; Ruci Arizanda Rahayu (International Journal of Artificial Intelligence for Digital Marketing, 2026)
Objective: Study this aim to analyze systematically the development of Internet Financial Reporting (IFR), factors that influence its implementation, as well as the impact on the market company. Method: Approach Systematic Literature Review (SLR) is used with follow PRISMA 2020 guide, which includes stages of identification, screening, assessment of eligibility, and inclusion. Of the 563 articles identified, 36 studies fulfil criteria and were analyzed further. Study data extracted using framework analysis, thematic, and cluster analysis to identify patterns and relationships between the draft.  Results:  Research results show three main. First, IFR determinants include characteristics of the company (size, profitability, leverage, liquidity), governance of companies, intellectual capital, and pressure institutions that have a significant to level IFR disclosure. Second, the implementation and quality of IFR varies widely between companies and countries, influenced by infrastructure technology, capabilities, source of power, human beings, and the equipment used for the information. Third, IFR has a proven positive impact positive to mark company through improving transparency, reducing information asymmetry, and providing a reinforcement signal to investors, even though a number of studies find an impact that is not significant.  Novelty: In a way, research This conclude that IFR is an instrument strategic in increase the quality of disclosure of companies and market perception of the company. These results give contribution for academics, practitioners, and regulators in understanding IFR dynamics as well as directing further development study furthermore.